Proceedings of the 2nd International Electronic Conference on Atmospheric Sciences 2017
DOI: 10.3390/ecas2017-04137
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drop Size Distribution Impact on Rainfall Interception by Trees

Abstract: Not all precipitation, falling above the trees, reach the ground. Part of it is retained in the canopy and eventually evaporates back into the atmosphere. This is known as intercepted rainfall. The process is influenced by various meteorological parameters of which we have mainly focused on drop diameter and velocity. Rainfall in the open and throughfall under birch and pine trees have been measured since 2014 in Ljubljana, Slovenia. The results demonstrate that birch has intercepted 41% (± 32%) and pine 70% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
3
2
0
Order By: Relevance
“…Larger drop size distribution during event C was observed sooner, from minutes 4 to 7, as well as increased throughfall under the pine trees by 26%. A similar increase of 28% and 20% of throughfall under pine trees, after the onset of larger and faster raindrops during June and July 2014 events, respectively, was reported also by Zabret et al [24]. On the other hand, no influence from changes in the drop size spectrum on throughfall under the birch trees was observed in this study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Larger drop size distribution during event C was observed sooner, from minutes 4 to 7, as well as increased throughfall under the pine trees by 26%. A similar increase of 28% and 20% of throughfall under pine trees, after the onset of larger and faster raindrops during June and July 2014 events, respectively, was reported also by Zabret et al [24]. On the other hand, no influence from changes in the drop size spectrum on throughfall under the birch trees was observed in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Throughfall under the pine trees after the occurrence of larger and faster drops immediately increased in both cases, but it exceeded the amount of rainfall in the open only in the case of event B (Figure 4). A similar phenomenon was also reported for the June 2014 event, which was 75 min long and delivered 10.2 mm of rainfall [24]. This may be the consequence of the time delay in the increase in the drop size spectrum and the amount of rainfall delivered until then (Figures 4 and 5).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Under dry conditions, interception rates are primarily controlled by rainfall intensity [14]. Although rainfall characteristics were considered to be the most influential variables, the number of raindrops, raindrop diameter, and velocity were hardly included in the analyses of rainfall effects on canopy interception [15][16][17], except for in a study by Zabret et al [17], who reported that raindrops with a larger diameter (6.5-8.5 mm) and higher velocity (7.6-10.4 ms −1 ) reduced canopy interception of rainfall.…”
Section: Introductionmentioning
confidence: 99%